2017
DOI: 10.2174/1745017901713010082
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Physical Activity Level, Mood and Anxiety States and Quality of Life in Physical Education Students

Abstract: Background:Physical activity level (PAL) is known to play an important role in reducing risk factors associated with sedentarism, in addition to improving the mental health and health-related quality of life (HRQL).Objective: Investigate the relationship of PAL and their domains with HRQL, mood state (MS) and anxiety. Method: 140 Physical Education students (23.6 ± 3.7 years) were evaluated. The Baecke Habitual Physical Activity and Quality of Life (QOL-36) questionnaires, State-Trait Anxiety Inventories (STAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 47 publications
5
25
1
6
Order By: Relevance
“…Most studies show a positive effect of sport activity on subjective well-being in terms of happiness and life satisfaction [35,36,37]. Our study results showed that they developed PA and QoL levels and that there was a positive correlation between them [38,39].…”
Section: Discussionsupporting
confidence: 54%
“…Most studies show a positive effect of sport activity on subjective well-being in terms of happiness and life satisfaction [35,36,37]. Our study results showed that they developed PA and QoL levels and that there was a positive correlation between them [38,39].…”
Section: Discussionsupporting
confidence: 54%
“…Our study found a relevant association overall between higher current PA and lower current perceived worse mood among the study sample; however, significant associations were solely observed among specific subgroups. Similarly, a significant body of work has observed improvements in mood state associated with higher levels of PA (34,35). Furthermore, not only were healthy populations that showed mood enhancement, but also populations with previous conditions (32,36); even short bouts of PA have been observed to improve mood in older adults (37).…”
Section: Current Perceived Moodmentioning
confidence: 99%
“…In addition, it is important to highlight the influence that teachers have on students' development of skills and knowledge based on a balance between discovery and previous experiences, which allows them to overcome difficulties and make the best decisions related to the adoption of behaviors that promote health [53,54]. In addition, PE is a discipline where students are exposed to continuous stressful situations and where, through the different proposed activities, they feel continually challenged, so success and failure are often present during classes [55][56][57]. Such circumstances can influence the opinion they have of PE classes, assuming a greater or lesser involvement of students during PE classes, affecting in the final stage the development of behaviors aimed at the adoption of healthy lifestyle habits.…”
Section: Discussionmentioning
confidence: 99%